2020
DOI: 10.1108/ijoa-02-2020-2038
|View full text |Cite
|
Sign up to set email alerts
|

HRM practices and organizational commitment link: maritime scope

Abstract: Purpose The purpose of this paper is to investigate the relationship between human resource management (HRM) practices bundles and organizational commitment, and find answers for questions on which of these bundles contribute how to the employees’ performance and loyalty according to their demographic characteristics in maritime market. Design/methodology/approach Two separate surveys were applied to 104 employees of international maritime companies. Factor and reliability analyses were carried out to ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Although, Thuan (2020) explains that knowledge sharing depends on the followers' creativity and stiff competition in managing the knowledge economy. Additionally, the previous study explored that affective organizational commitment was found to have mediated the link between SHR practices and tacit knowledge sharing (Anvari et al, 2014;Aydo gan and Arslan, 2020). Another study supported the fully mediated link of organizational commitment between authentic leadership and turnover intention (Kim, 2016).…”
Section: Mediation Of Affective Organizational Commitment Between Aut...mentioning
confidence: 95%
See 1 more Smart Citation
“…Although, Thuan (2020) explains that knowledge sharing depends on the followers' creativity and stiff competition in managing the knowledge economy. Additionally, the previous study explored that affective organizational commitment was found to have mediated the link between SHR practices and tacit knowledge sharing (Anvari et al, 2014;Aydo gan and Arslan, 2020). Another study supported the fully mediated link of organizational commitment between authentic leadership and turnover intention (Kim, 2016).…”
Section: Mediation Of Affective Organizational Commitment Between Aut...mentioning
confidence: 95%
“…Moreover, it assures the employees of better safety measures (Walumbwa et al , 2014). Besides, Aydoğan and Arslan (2020) suggest that HRM practices can be best explained and managed through authentic leadership because the leaders transform the behavioral tendency of the followers although, the organizational culture always needs authentic leadership (Tran, 2020). Hadian Nasab and Afshari (2019) also argue that authentic leadership elucidates the transparency and behavioral authenticity of the philosophy of knowledge.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Vivid implementation of effective HRM practices contributes to generating desired committed behavior of employees. The impact of some HRM practices such as performance-based rewards, information sharing, training programs, and pay policies is stronger on overall organizational commitment (Aydoğan & Arslan, 2020). Highly motivated, skilled, and satisfied employees are outcomes of implementing HRM practices that enhance employees' commitment to their organization and direct their efforts towards goal accomplishment (Sriviboon & Jermsittiparsert, 2019).…”
Section: Hrm Practices and Organizational Commitmentmentioning
confidence: 99%
“…Previous studies revealed that positive organizational practices were significantly related to work engagement, task performance, and social climate [21]. However, even though positive practices receive increased attention from researchers [14][15][16][17][18][19][20][21][25][26][27], there is a lack of research on the specifics of positive organizational practices in public and private sector organizations. Exploring positive organizational practices in the public and private sectors and analyzing the links to the possibly related variables might provide supplemental information on the contributing factors.…”
Section: Positive Organizational Practicesmentioning
confidence: 99%